1995
DOI: 10.1111/j.1365-2621.1995.tb09844.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Cultured and Wild Sturgeon (Acipenser oxyrinchus desotoi) Based on Fatty Acid Composition

Abstract: Sturgeon species have attracted interest for aquaculture due to high value of the flesh, caviar and wild stock depletion. Lipid was extracted from sturgeon muscle using the Bligh and Dyer procedure. Fatty acids from total lipid were methylated using boron-trifluoride in methanol. Fatty acid methyl esters were analyzed by gas chromatography as weight %. The fatty acid profiles of lipids were different between cultured and wild sturgeon. Wild sturgeon had higher levels of 16:0, 16:107, 18:109, 22: 4~6 and 22:50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
2
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 22 publications
5
43
2
3
Order By: Relevance
“…The levels of EPA and DHA in seawater fish are higher than those in freshwater fish (Czesny et al, 1999). In the present study, EPA and DHA contents in dorsal muscle from large yellow croaker were particularly abundant, consistent with previous findings that they were higher than those from any other cultured fish (Chen et al, 1995;Karahadian et al, 1995;Paleari et al, 1997).…”
Section: Discussionsupporting
confidence: 81%
“…The levels of EPA and DHA in seawater fish are higher than those in freshwater fish (Czesny et al, 1999). In the present study, EPA and DHA contents in dorsal muscle from large yellow croaker were particularly abundant, consistent with previous findings that they were higher than those from any other cultured fish (Chen et al, 1995;Karahadian et al, 1995;Paleari et al, 1997).…”
Section: Discussionsupporting
confidence: 81%
“…It was reported that DHA decreases the concentration of low density lipoprotein cholesterol in plasma [15], and EPA is recognized as the most important essential fatty acid of the n -3 series in the human diet because it is the precursor to the 3-series eicosanoids [16]. On the contrary the saturated fatty acids cause a raise in the blood cholesterol level because are easily deposited on the walls of the arteries.…”
Section: Resultsmentioning
confidence: 99%
“…If a lobster missed data from one variable it was excluded from the discriminate analysis. Ideally, this sort of work is better suited to a single instrument returning a number of values for each example or individual, for example, veterinary blood panels, HPLC, gas chromatography, or reflectance spectroscopy (Girard & Nakai 1994a;Chen et al 1995Chen et al , 2003Downey & Beauchene 1997).…”
Section: Discussionmentioning
confidence: 99%